PERSONAL DATA PROTECTION IN THE PROVISION OF ARTIFICIAL INTELLIGENCE VOICE GENERATOR AND DEEPFAKE APPLICATIONS IN INDONESIA - Putri Mega Citakhayana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Nowadays, the development of AI has brought miracles, including the existence of applications that can imitate a person's voice and face. For example, former President Jokowi whose voice is used as if singing a song. There is even a video of former President Jokowi giving a speech in Chinese, even though in fact he never sang a song or gave a speech. This can apparently be done through an AI application using a person's voice and facial image. Even though after the issuance of Law No. 27 of 2022 concerning Personal Data Protection (UUPDP), a person's voice and image are included in personal data in the form of biometrics. Then today, the development of technology in the digital era has made it common to use portraits to use AI Voice Generators and Deepfakes without permission. Deepfake itself is an image and video produced by Artificial Intelligence as if it were real. The PDP Law itself prohibits the use of a person's biometric data. For this reason, it is necessary to research the legal protection of personal data in the form of voices that are changed using AI Voice Generators or faces into Deepfake form. In addition, the use of personal data is very high, for example to attract buyers on digital platforms by creating deepfakes using portraits taken randomly on the Internet without the consent of the owner of the personal data.